Optimal linear control design applied to the synchronism of vocal folds with asymmetric stiffness - Souza e Silva Alarcao, Sunamita [UNESP]; Chavarette, Fabio Roberto [UNESP]; Vandana (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2020)
The emission of sounds is an important means of communication between animals, which helps them to find a partner, establish their territory, and even alert other members of a population about a possible threat. In human beings, the emission of sounds allows an even more specialized communication, because it possibly render a wide exchange of ideas and knowledge. The most important process related to voice emission is the movement of vocal folds. Therefore, their proper functioning is essential for the emission of sounds. Vocal folds possess a muscular tissue, and are located inside the larynx. When air passes through them, they vibrate, thus emitting the sound by which we communicate. The vocal folds are elastic fibers that distend or relax under the action of the larynx muscles, thus modulating and modifying the sound as we speak or sing, for example. This complex process is modeled by a system of differential equations. In this paper, we present a study about asymmetric vocal folds, where a difference in their stiffness is considered. The objective of this study is to synchronize the movement of vocal folds caused by that asymmetry through the optimal linear control method, showing their functioning for different values of stiffness for each vocal fold. In this way, the control design has shown to be efficient, producing a good functioning of the vocal folds and rendering the emission of sound possible even in diseased vocal folds.
Keywords: control method; lyapunov exponents; chaos; LQR; asymmetry